Effects of oral organic arsenic exposure on paraoxonase 1 (PON1) activity and atherogenesis - Adekunle, Ishola Afeez (Kulliyyah of Medicine, International Islamic University Malaysia, 2016)
Oral exposure to arsenic through drinking water is threatening human lifes worldwide through human activities. Previously, organic arsenic was thought to be less toxic than its inorganic counterpart until recent studies suggested that they may be equally toxic. Although restricted in some countries, monosodium methylarsonate (MSMA) is a potent organoarsenical content of herbicides used in many countries, mostly Asian countries. Epidemiological studies have linked high-chronic inorganic arsenic exposure with atherosclerosis but so far no report to relate the effect of organic arsenic with atherosclerosis. Paraoxonase 1 (PON1) is an esterase enzyme that suppresses oxidised LDL generation, thereby preventing atherosclerosis. Since MSMA is still popularly used and produced particularly in Malaysia, this current study aimed to investigate the effect of oral administration of organic arsenic, MSMA on PON1 activity, lipid peroxidation, liver enzyme and the development of atherosclerosis in rats. Fifty-five Sprague Dawley rats were divided into five groups (n=11) including a control group, treatment 1 (T1), treatment 2 (T2), treatment 3 and treatment 4. Treatment groups were given daily oral MSMA doses of 42.13, 63.20, 126.4 and 210mg/kg body weight of MSMA respectively for 16 weeks. Rats in Treatment groups 3 and 4 were noted to have high mortality due to severe diarrhea and drastic weight reduction, and therefore were discontinued from this study. Serum paraoxonase and arylesterase activities were measured spectrophotometrically while Ox-LDL levels as well as MDA were measured by ELISA and spectrophotometric methods respectively. Serum AST, ALT and lipid profiles were analysed using automated chemistry analyser. Histomorphometric evaluation of aorta was assessed by using H&E, VVG staining and immunohistochemistry for VCAM-1 and ICAM-1. The results showed that PON:Ox-LDL ratio was significantly reduced (p<0.05) while Ox-LDL and MDA were significantly higher (p<0.05) in Treatment groups as compared to that of control group. Hepatic enzymes (AST and ALT) were not significantly affected by MSMA treatment. Microscopically, Treatment groups showed early atherosclerosis changes with intima layer thickening and positive VCAM-1 and ICAM-1 expressions. Therefore, the development of early atherosclerosis seen in chronic MSMA exposure may be explained by inability of PON1 to hydrolyse oxidised LDL.